F Formulasi Dan Evaluasi Fast Disintegrating Tablet (FDT) Dari Ekstrak Daun Pepaya (Carica Papaya L.) Dengan Variasi Konsentrasi AC-DI-SOL Sebagai Superdisintegran - Kamalia, Hasna; Noval, Noval; Darsono, Putri Vidiasari (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: One of the risk factors that can cause an increase in the incidence of morbidity and mortality in patients with hypertension is patient non-adherence in taking antihypertensive drugs. As we get older, there is a decrease in the function of the tongue in achieving muscle pressure to make effective movements, which can cause difficulty swallowing drugs in solid dosage forms. This can be overcome with FDT preparations which can be disintegrated in the mouth without having to use water. Objectives: To compare the evaluation results of fast disengtengrating papaya leaf tablet formulation (Carica papaya L.) and to determine the effect of Ac-Di-sol concentration from fast desingtengriting tablet (Carica papaya L.) preparation Method: The method used is a quasi-experimental design with a non-equivalent control group design by comparing the results of the intervention with a control group from the formulation evaluation. Results: The tablet hardness test (hardness tester) obtained a significance result of 0.17 <0.05, which means that there is a difference in tablet hardness in all formulas. In the friability tester, the significance results were obtained for formula I, namely in formula III with a significance value (sig) of 0.000 <0.05, which means that the fragility data did not spread normally in all formulas. At the time of disintegration, a significant result of 0.027 < 0.05 was obtained, which means that there was a difference in the disintegration time of the tablets in each formulation. In the disintegration time test, a significance result of 0.139 <0.05 was obtained, which means that there is a difference in each disintegration result in all formulas. In the wetting time test, the significance result was 1.7 < 0.05, namely the wetting test aimed to determine the time required for the tablet to be wetted by water. So it can be said that there are significant differences in each formulation. Conclusion: Based on the results of the organoleptic test, all of the tablet formulations produced had a brown color, with a bitter taste, smelled of mint and papaya extract and were round in shape. The combination of the concentration ratio of Ac-Di-Sol and Mannitol has the effect of evaluating friability, hardness, disintegration time and wetting time on Fast Disintegrating Tablets Papaya leaf extract (Carica papaya L.) Formulation III with 5 mg Ac-Di-Sol is the most effective formulation. optimal for Fast Disintegrating Tablets Papaya leaf extract (Carica papaya L.).